ANALISIS PROSPEK USAHA BUDIDAYA UDANG VANNAMEI DI KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Rumaijuk, Adol Frian; Lubis, Satia Negara (JURNAL PROINTEGRITA, 2020)
Vannamei shrimp Aquaculture business opportunities in Indonesia are getting better. Great potential for Vannamei shrimp development is owned by Langkat Regency, North Sumatra Province. This study aims at analyzing the business by identifying internal and external environmental factors that influence the development of Vannamei shrimp culture and formulate alternative strategies that can be applied in the development of Vannamei shrimp culture in Langkat Regency. Quantitative analysis was applied to determine the internal and external environment in the form of strengths, weaknesses, opportunities, threats and SWOT analysis. IFE Matrix, EFE Matrix, IE Matrix, and QSP Matrix are used for quantitative analysis. The IFE and EFE matrices show that this business has internal and external conditions at a moderate and average position. It was found that the best strategy was to maintain and develop the business horizontally according to the IE Matrix. The SWOT matrix recommends six alternative strategies that can be grouped, namely: Increase production and land use potential. The priority strategy in this study using the QSP Matrix is ​​to maintain production stability.